Activity of the Hypothalamic Melanocortin System Decreases in Middle-Aged and Increases in Old Rats. (1st November 2017) - Füredi, Nóra; Mikó, Alexandra; Gaszner, Balázs; Feller, Diána; Rostás, Ildikó; Tenk, Judit; Solymár, Margit; Balaskó, Márta; Pétervári, Erika
Abstract: Appearance of middle-aged obesity and aging anorexia both in humans and rodents suggests a role for regulatory alterations. Hypothalamic melanocortin agonist, α-melanocyte-stimulating hormone (α-MSH) produced in the arcuate nucleus (ARC), reduces body weight via inducing hypermetabolism and anorexia mainly through melanocortin 4 receptors (MC4Rs) in the paraventricular nucleus (PVN). Orexigenic ARC-derived agouti-related protein (AgRP) is an inverse agonist on MC4R in the PVN. Previously, we demonstrated that characteristic age-related shifts in the catabolic effects of α-MSH may contribute both to middle-aged obesity and aging anorexia. Responsiveness to α-MSH decreases in middle-aged rats compared with young adults, whereas in old age it rises again significantly. We hypothesized corresponding age-related dynamics of endogenous melanocortins. Therefore, we quantified mRNA gene expression and peptide or protein level of α-MSH, AgRP, and MC4R in the ARC and PVN of male Wistar rats of five age groups (from young to old). Immunofluorescence and quantitative reverse transcriptase polymerase chain reaction were applied. α-MSH and MC4R immunoreactivities in the ARC and PVN declined in middle-aged and increased together with their expressions in aging rats. AgRP gene expression but not its immunoreactivity increased in aging rats. Our results demonstrate that age-dependent changes of endogenous melanocortins contribute to middle-aged obesity and aging anorexia.